2011
DOI: 10.1177/0956797611414726
|View full text |Cite
|
Sign up to set email alerts
|

A Single Exposure to the American Flag Shifts Support Toward Republicanism up to 8 Months Later

Abstract: There is scant evidence that incidental cues in the environment significantly alter people's political judgments and behavior in a durable way. We report that a brief exposure to the American flag led to a shift toward Republican beliefs, attitudes, and voting behavior among both Republican and Democratic participants, despite their overwhelming belief that exposure to the flag would not influence their behavior. In Experiment 1, which was conducted online during the 2008 U.S. presidential election, a single e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 19 publications
6
97
1
Order By: Relevance
“…Research has begun to investigate neural activation that underlies the processing of political attitudes and preferences (Amodio et al, 2007;Zamboni et al, 2009), including studies on deliberative processing of political statements and simulated voting for political candidates (Westen et al, 2006;Spezio et al, 2008;Gozzi et al, 2010;Bruneau and Saxe, 2010;Rule et al, 2010).Yet the neural substrate underlying automatic processing of political preferences (Todorov et al, 2005;Ballew and Todorov, 2007;Berger et al, 2008;Galdi et al, 2008;Hassin et al, 2007;Carter et al, 2011;Healy et al, 2010) remains largely unstudied. Extending earlier fMRI studies, the present studyshowed that brain responses can reflect individual political preferences -for politicians and associated parties -in the absence of conscious deliberation and attention.…”
Section: Discussionmentioning
confidence: 99%
“…Research has begun to investigate neural activation that underlies the processing of political attitudes and preferences (Amodio et al, 2007;Zamboni et al, 2009), including studies on deliberative processing of political statements and simulated voting for political candidates (Westen et al, 2006;Spezio et al, 2008;Gozzi et al, 2010;Bruneau and Saxe, 2010;Rule et al, 2010).Yet the neural substrate underlying automatic processing of political preferences (Todorov et al, 2005;Ballew and Todorov, 2007;Berger et al, 2008;Galdi et al, 2008;Hassin et al, 2007;Carter et al, 2011;Healy et al, 2010) remains largely unstudied. Extending earlier fMRI studies, the present studyshowed that brain responses can reflect individual political preferences -for politicians and associated parties -in the absence of conscious deliberation and attention.…”
Section: Discussionmentioning
confidence: 99%
“…Flag influence on USA elections was also studied when Barack Obama was leading the presidential race of 2008 (Carter et al, 2011). Advertising techniques have repeatedly shown that in order to influence public audiences there is nothing better than perceptual saturation.…”
Section: Flag Pressure and Intimidationmentioning
confidence: 99%
“…Participants who received a single exposure to an American flag exhibited a significant increase in Republican voting intentions, voting behavior, political beliefs, and implicit and explicit attitudes, with some e↵ects lasting 8 months after the initial priming episode Carter et al (2011).…”
Section: Introductionmentioning
confidence: 99%